O desenvolvimento da percepção intercultural no processo de aprendizagem de espanhol como língua estrangeira: um estudo sobre potencialidades da mediação fílmica - Quiroga, Valeria Verónica (2014)
The theme of this research arises from the researcher s experience as a teacher of Spanish as a Foreign Language (SFL). This debate specifically began by problematizing cinema as a supporting and complementary teaching resource to the process of teaching and learning a language. The sociolinguistics of Dell Hymes (1971) subsidizes us with the theoretical elements to link the questions that compound the subject of this investigation. The scope of this research involves: 1) analyzing two films from the New Argentine Cinema, showing them as disseminators of identity and cultural characteristics of the country; 2) answering how cinema as a disseminator of these characteristics can influence intercultural awareness of Spanish as a Foreign Language learners. Examples in Hymes s sociolinguistic theory are scenic and denote the critical point that justifies this investigation. Moreover, this approach reveals an intercultural aspect, considering the exchange between both cultures we will present the expressions Brasilidade and Argentinidade and how these perceptions are understood by the learners of SFL. We used two films: Historias Mínimas (2002) and El Camino de San Diego (2006) both directed by Carlos Sorin. These films were chosen for two reasons: a) Due to references to Brazil that appear in the film; b) both films were shot in regions that are distant from the capital of Argentina, so it broadens the perspectives of the learner about the country s culture. Our intention with the focus on both films was to verify previous social representations about the aspects of the culture of each country Brazil as the country of the learners and Argentina as the country of the selected films. For data analysis we used the theory of social representations of Moscovici (2012). Secondly, a discussion was developed following the methodological guidance of focus group, in order to verify the speech of learners and their perception regarding the intercultural aspects verified in the films. The development of this research was based on the studies of cinema of Sadoul (1960), Pujol Ozonas (2011), Costa (1985), Amado (2009), Tranchini (2007), Ferro (1991), film as a documentary source by Dabul and Bauer (2008), as well as the studies in which cinema is associated to teaching practice in the context of Foreign Language teaching, such as Lonergan (1984), Ruiz Fajardo (1993), Napolitano (2003), Garcia-De-Stefani (2010), among others. Furthermore, we deal with studies on culture based on Thompson (2011), Geertz (1973), Malinowski (1960,1986) and Viana (2003), on identity perspectives, by Hall (2005, 2009), Cardoso de Oliveira (1976), Barros (2009), Vargas (2007), Shumway (2008) and on intercultural competence by Byram (1995, 1997), Alsina (1999) and Oliveras (2000), that Santos (2004) calls intercultural communicative approach, implying a dialogue of cultures.